A Reciprocal Intercommunication between Reader and Writer: A Critical Study of Cyber Literature (European journal of volunteering and community-based projects, 2022)
Since the accessibility of the internet, cyber literature can be an act of bringing ease, evolving preferences and mindsets. This research may be a survey focused on the opinions of the respondents on the nature of social media cyber literature; of its gain and effect on the reader. This research is limited to the collective poems on Facebook. The logic is simple; the shortened version is preferred. Poetry is more likely to be used for the interpretation of reader-writer interactivity in cyber literature. The technique is the literary theory of reader reaction with attention to Facebook's reader-writer personalization. The objectives of this article were to expose the impetus of audiences to react to the submitted text, the reasons why they really like, and what its benefits are. The findings showed that cyber literature is effective in implementing a substitute writing style that also improves writers’ enthusiasm and imagination to make use of the digital content.